Studi analisis Bibliometrik dan Sistimatik Literatur Review pada Wireless Power Transfer di Peralatan Kesehatan Implan - Yuliandoko, Herman; Hidayat Kusuma, Dedy; Hilmi, Mustofa (Applied Information Technology and Computer Science (AICOMS), 2025)
This study conducted a bibliometric and systematic literature review analysis related to Wireless Power Transfer (WPT) which is currently a research trend in the application of embedded medical devices in the patient's body. Using the VoS Viewer tool for visualization of bibliometric network analysis and R Studio for statistics, this study aims to identify key trends, research gaps, and research directions and opportunities in the field of WPT for implantable medical devices. The results of the analysis show that topics related to the use and efficiency of WPT technology in medical applications and implantable devices are often the focus of the existing literature. Research related to power transfer and biomedical implants is the main subject in the development of WPT technology, especially in improving power transfer efficiency, reducing electromagnetic interference to patients or SAR, and optimizing device design. The research gap found is related to the need to develop a smaller, more efficient WPT system that is able to meet the needs of long-term implantable medical devices. Future research opportunities include improving flexible implant technology, more efficient power delivery, and developing WPT systems for wider medical applications.